2013
DOI: 10.4103/1319-3767.121036
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of resectability of pancreatic adenocarcinoma

Abstract: Background/Aims:Identifying patient-related factors as well as symptoms and signs that can predict pancreatic cancer at a resectable stage, which could be used in an attempt to identify patients at an early stage of pancreatic cancer that would be appropriate for surgical resection and those at an unresectable stage be sparred unnecessary surgery.Materials and Methods:A retrospective chart review was conducted at a major tertiary care, university hospital in Riyadh, Saudi Arabia. The study population included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This is due to, at least in part, increased cigarette smoking and alcohol consumption in males. [33][34][35][36] The results showed that the proportion of PDAC patients with diabetes mellitus was 23.9%, which is comparable to that reported by several authors. 1,22,28 Similar to the findings of other studies, the presenting symptoms for PDAC were dominated in our series by weight loss (68.6%), abdominal pain (64.2%) and jaundice (53.7%).…”
Section: Discussionsupporting
confidence: 74%
“…This is due to, at least in part, increased cigarette smoking and alcohol consumption in males. [33][34][35][36] The results showed that the proportion of PDAC patients with diabetes mellitus was 23.9%, which is comparable to that reported by several authors. 1,22,28 Similar to the findings of other studies, the presenting symptoms for PDAC were dominated in our series by weight loss (68.6%), abdominal pain (64.2%) and jaundice (53.7%).…”
Section: Discussionsupporting
confidence: 74%
“…Few studies have looked at symptoms and the duration of symptoms on PDAC disease progression, resectability and survival, and reportedly clinical presentation had no impact on resectability or survival [ 11 , 12 ]. No studies from Sub-Saharan Africa have investigated the association between symptoms and disease progression or prognosis in PDAC.…”
Section: Introductionmentioning
confidence: 99%
“…The details of the selection process are shown in Figure 1. The remaining 12 articles were screened by full text; finally, eight articles were included in the quantitative synthesis [9][10][11][12][13][14][15][16].…”
Section: Search Resultsmentioning
confidence: 99%